Implementasi Business Intelligence untuk Mendukung Pengambilan Keputusan Strategis Sumber Daya Manusia di Universitas Pancasila - Nur Laila Afnash; Wargijono Utomo (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Human Resource (HR) management in universities requires a data-driven strategic decision support system. Universitas Pancasila faces challenges in monitoring employee performance, turnover, and training effectiveness due to fragmented data across multiple systems. This study implements a Business Intelligence (BI) system to support HR strategic decision-making. A star-schema Data Warehouse was built by integrating data from SIMPEG, e-Learning, and Payroll systems through Extract, Transform, Load (ETL) processes, yielding 4,217 employee records over 2021–2023. An interactive dashboard was developed to visualize four KPI categories: employee performance, turnover, training, and workforce distribution. System evaluation used the Technology Acceptance Model (TAM) with 35 respondents, achieving a Perceived Usefulness score of 4.21 and Perceived Ease of Use of 4.08 (scale 1–5). KPI results showed overall performance at 78.6%, turnover rate of 8.3%, and training completion at 71.4%. The BI system enabled HR leadership to identify underperforming units and formulate targeted interventions, reducing manual reporting time by 65%.